2004
DOI: 10.2337/diacare.27.1.201
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Myocardial Infarction Case Fatality and Stroke Case Fatality in Type 2 Diabetes

Abstract: OBJECTIVE -Patients with diabetes have a higher case fatality rate in myocardial infarction (MI) or stroke than those without diabetes: that is, MI and stroke are more often fatal if diabetes is present. We investigated whether the risk of MI or stroke being fatal in type 2 diabetes can be estimated using information available around the time diabetes is diagnosed.RESEARCH DESIGN AND METHODS -Analyses were based on 674 cases of MI (351 fatal) that occurred in 597 of 5,102 U.K. Prospective Diabetes Study (UKPDS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
155
2
7

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 256 publications
(165 citation statements)
references
References 65 publications
1
155
2
7
Order By: Relevance
“…Risk prediction equations have also been developed specifically for individuals with diabetes [9,[11][12][13]. The best known are those of the UK Prospective Diabetes Study (UKPDS) [9,11].…”
Section: Introductionmentioning
confidence: 99%
“…Risk prediction equations have also been developed specifically for individuals with diabetes [9,[11][12][13]. The best known are those of the UK Prospective Diabetes Study (UKPDS) [9,11].…”
Section: Introductionmentioning
confidence: 99%
“…History of smoking was positive in 60% and most was current smoker. A study done in Yemen 15 showed the incidence of smoking was less than that of our study. Other risk factors such as obesity, sedentary life also seemed to present.…”
Section: Discussionmentioning
confidence: 47%
“…Such result in accordance with previous observation emphasizes the fact that diabetes and hypertension are associated. 15 In this study, most of the patient were hypertensive and most had uncontrolled blood pressure. History of smoking was positive in 60% and most was current smoker.…”
Section: Discussionmentioning
confidence: 99%
“…In patients with disturbances of carbohydrate metabolism the course of stroke is worse, the period of rehabilitation is longer and the mortality rate is higher. 9,[15][16][17][18][19] The severity of stroke in diabetes is explained by a cluster of factors termed 'metabolic syndrome', that is characterised by insulin resistance, hyperinsulinaemia, hyperglycaemia, arterial hypertension, obesity and dyslipidaemia. All these factors promote vascular injury: not only do they increase the risk of stroke but they also account for the severity of disease.…”
Section: Discussionmentioning
confidence: 99%